Structure of a putative β-phosphoglucomutase (TM1254) from Thermotoga maritima - Strange, Richard W. (International Union of Crystallography, 2009)

(untitled)
The structure of TM1254, a putative β-phosphoglucomutase from T. maritima, was determined to 1.74 Å resolution in a high-throughput structural genomics programme. Diffraction data were obtained from crystals belonging to space group P22(1)2(1), with unit-cell parameters a = 48.16, b = 66.70, c = 83.80 Å, and were refined to an R factor of 19.2%. The asymmetric unit contained one protein molecule which is comprised of two domains. Structural homologues were found from protein databases that confirmed a strong resemblance between TM1254 and members of the haloacid dehalogenase (HAD) hydrolase family.